Benthic Diatoms Composition of Sungai Sarawak Kanan and Its Tributaries - Nur Amira Yasmin, Binti Mohd Yusoff (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study aimed to document the composition of benthic diatoms at Sungai Sarawak Kanan and its tributaries. Samplings were done in November 2013, January 2014 and March 2014 at three stations namely Sungai Pedaun, Sungai Bijuray and Sungai Sarawak Kanan. Diatoms samples were cleaned with Hydrogen Peroxide oxidation method and mounted with high refractive medium Naphrax® on a glass slide to facilitate cell identification. A total of 21 genera were recorded in this study with the most number at Station 1. There are three common genera were found at each station throughout the study, which are Achnanthes, Gomphonema and Navicula. The correlation among physico-chemical water quality parameter with some diatom genus was identified to have strong significant correlation with p< 0.05 (Pearson’s Correlation). The physico-chemical water quality parameter is measured in range of 5.83 ppm to 11.79 ppm for dissolved oxygen (DO), 25.0 ºC to 29.73 ºC for temperature, 7.02 to 7.88 for pH, and 37.9 μS/cm to 114.90 μS/cm for conductivity.